The Role of Civil Servant Investigators (PPNS) of the Department of Environment and Forestry (DLHK) in Handling Environmental Crimes Committed by Corporations: A Green Criminology Study in Pelalawan Regency - Natasyah, Arsyllia; Rio Tutrianto (Sisi Lain Realita, 2026)
This study examines the role of Civil Servant Investigators (PPNS) from the Department of Environment and Forestry (DLHK) in addressing corporate crimes that cause environmental damage in Pelalawan Regency. The study employs a green criminology perspective. Plantation and forestry activities give rise to issues such as waste pollution, deforestation, and permit violations. These issues impact ecosystems and communities. This descriptive qualitative study collected data through interviews, observations, and documentation. Data were gathered from PPNS, law enforcement officials, and affected communities. The findings indicate that PPNS play a crucial role in enforcing both administrative and criminal laws. However, PPNS face significant limitations. Human resources, facilities, evidence collection, and inter-agency coordination remain suboptimal. Green criminology emphasizes that environmental crimes threaten ecological justice. Because environmental crimes threaten ecological justice, law enforcement must be comprehensive. The study recommends enhancing the capacity of the PPNS, strengthening inter-agency coordination, and implementing firm policies focused on environmental restoration to achieve ecological justice.